Antioxidants for Skin Health - Kumar, Virender; Tanwar, Neha; Goel, Muskan; Khan, Mohit; Kumar, Davinder; Singh, Gajendra; Mundlia, Jyoti; Khatri, Naveen; Kumar, Ashwani (Recent Advances in Food Nutrition & Agriculture, 2025)
Antioxidants play a pivotal role in maintaining skin health and integrity, combating the deleterious effects of oxidative stress induced by environmental aggressors such as UV radiation, pollution, and lifestyle factors. This paper reviews the contributions of key antioxidants, including Vitamin C, Vitamin E, Vitamin A, green tea extract, Coenzyme Q10, Resveratrol, Selenium, and Polyphenols, in skin health care. Vitamin C, known for its collagen synthesis promotion and photoprotection properties, alongside Vitamin E, a lipid-soluble antioxidant, synergistically works to neutralize free radicals and repair damaged skin cells. Vitamin A, in the form of retinol, plays a critical role in skin cell regeneration and the maintenance of skin integrity. Green tea extract, rich in Polyphenols, offers anti-inflammatory and anticarcinogenic properties, making it a potent ingredient for skin protection. Coenzyme Q10, a naturally occurring antioxidant in the body, aids in energy production for cell repair and regeneration, while Resveratrol, found in grapes and berries, provides anti-ageing benefits by enhancing skin's resistance to oxidative stress. Selenium, an essential mineral, contributes to the protection of skin cells from oxidative damage. The incorporation of these antioxidants in skincare products and dietary sources is discussed, highlighting the importance of a holistic approach in skincare regimes. The paper emphasizes the synergy between topical applications and dietary intake of antioxidants, advocating for a comprehensive strategy for promoting skin health and preventing age-related skin alterations.MethodsFor the review article, a variety of search engines and databases were used to identify relevant articles. Furthermore, for biomedical literature focusing on antioxidants and their effects on skin health, PubMed was used. Moreover, to access a wide range of scholarly articles, including those related to dermatology and skincare, Google Scholar was used. Scopus provides comprehensive coverage of peer-reviewed literature across various scientific disciplines. Web of Science identifies high-impact articles and research on antioxidants in skincare. In addition, for accessing full-text articles on antioxidants and their applications in dermatology, Science Direct was used. The inclusion criteria for the review paper were as follows: only studies published in peer-reviewed journals were included to ensure the credibility and reliability of the information. Articles published in English were considered, to avoid language-related biases and ensure comprehension. Studies published within the last 10 years were included to provide the most current insights into antioxidant research in skincare. Articles must specifically focus on the role of antioxidants (Vitamin C, Vitamin E, Vitamin A, green tea extract, Coenzyme Q10, Resveratrol, Selenium, Polyphenols) in skin health care. Both experimental studies (in vivo and in vitro) and clinical trials were included to provide a comprehensive overview of the antioxidant effects. Full-text articles were included to allow for thorough data extraction and analysis. The exclusion criteria for the review paper were as follows: Publications that were not peer-reviewed, such as editorials, opinion pieces, and non-scholarly articles, were excluded. Articles published in languages other than English were excluded due to potential translation challenges and to maintain consistency. Studies that did not focus on the specified antioxidants or their impact on skin health were excluded. Duplicate publications were excluded to avoid redundancy in the review. Articles with insufficient or incomplete data were excluded to ensure the quality and reliability of the review findings.
Keywords: oxidative stress